Lead Removal by Nano-Scale Zero Valent Iron: Surface Analysis and Ph Effect - Rubio-Campos, M; Altbir-Drullinsky, D; Baltazar-Rojas, S; Arancibia-Miranda, N; Arancibia-Miranda, N (Elsevier Ltd, 2014)
The use of nano-scale zero valent iron (nZVI) in the removal of Pb 2+ from aqueous solution is studied as a function of pH, evaluating the structural and surface changes of the nZVI, as well as its magnetic properties after the sorption process. The kinetics of the removal process of Pb2+ by nZVI was studied as a function of pH, where the pseudo second order (PSO) kinetics model reproduces the experimental results, with an initial adsorption (h) at pH 4 almost three times greater than at pH 6.0. From the sorption isotherm results, we find an enhanced sorption capacity as pH is increased. The Langmuir model is in good agreement with our experimental data, where a maximum sorption capacity is found to be 50.31 ± 2.36 and 32.85 ± 3.87 (mg g-1) at pH 6 and 4, respectively, suggesting the formation of new active sites on the external surface of the nZVI. The XRD results, obtained from the samples after removal of Pb2+, show new mineral phases of nZVI, which can be attributed to Fe and Pb polycrystals. These results obtained from the samples, before and after Pb2+ sorption at different pH values, indicate that these values conditioned the surface and morphological changes observed in nZVI, even modifying their magnetic properties. © 2014 Elsevier Ltd.